THE EFFECT OF NET INTEREST MARGIN (NIM) AND OPERATIONAL COSTS OF OPERATIONAL INCOME (BOPO) ON RETURN ON ASSETS (ROA) OF SHARIA BANKS - Mardahleni Mardahleni; Wahmita Arsandi (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2019)
Abstract Return On Asset is one of the most important ratios for any financial institution or company because it deals with the sustainability and stability of any financial institution or company. In addition, for measuring the company's ability to generate profits derived from investment activities. To generate a high profit per period, companies need to pay attention to all factors that affect Return on Assets. The purpose of this research is to find out (1) The effect of Net Interest Margin (NIM) on Return On Asset (ROA) (2) The effect of Operational Cost Of Operating Income on Return On Asset (ROA) (3) The effect on Net Interest Margin (NIM) and Operational Cost Of Operating Income on Return on Asset (ROA). The research that the writer conducted is on the Bank listed on the Indonesia Stock Exchange namely Syariah Commercial Bank Period 2014-2016. The population of this study is the financial statements of Syariah Commercial Banks listed on Indonesia Stock Exchange Period 2014-2016. The sample is financial report at Syariah Commercial Bank during period of 2014-2016. Sampling technique is purposive sampling, data collection using documentation, data analysis using multiple regression that is Y = 3.0170 + 0,040X1 + 0,005X2 + e indicate that Net Interest Margin has positive but insignificant effect with 0,773 and significant rate 0,452 (> 0,05 ). Operational Cost Of Operating Income cost has positive but insignificant effect with 0,865 and significant rate 0,401 (> 0,05). Net Interest Margin (NIM) and Operational Cost Of Operating Income simultaneously have positive but insignificant effect with coefficient of 0,194 and significant rate 0,198. Net Interest Margin (NIM) and Operational Cost Of Operating Income 19.4% the remaining 80.6% again influenced by other variables which is not included in this test.